Pengembangan Warisan Budaya Tambang Batubara Ombilin Kota Sawahlunto - Velin Perdiana; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study describes the development of the cultural heritage of the Ombilin coal mine in Sawahlunto City. The background of this research is, the lack of public awareness in managing world heritage sites, limited human resources, and limited facilities and infrastructure. The formulation of the problem in this research is how to develop the cultural heritage of the Ombilin coal mine in Sawahlunto City and what are the factors that influence the implementation of the development of the cultural heritage of the Ombilin coal mine in Sawahlunto City and studied using Collaborative Governance theory. This research was conducted with a descriptive qualitative method. The selection of informants was carried out by purposive sampling technique, and to test the validity of the data using triangulation techniques. Data was collected by means of interviews, documentation studies and observations. Data analysis technique is done by data reduction, data presentation, data verification. The results of the study indicate that the development of the Ombilin coal mine cultural heritage can be said to have been carried out well, although in its development there are still shortcomings and obstacles faced.